Electronic frailty index : a population approach to improving health and wellbeing in health and social care for falls and frailty /: a population approach to improving health and wellbeing in health and social care for falls and frailty. ([2017?]) - McInally, Lianne; Moss, Deirdre; Devereux, Nathan
No abstract available